Ballad-like Parallels in the (Auto)biographies of the Folk Singers - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2016)
The author of the article aims at seeking individual connections between folk ballads, characterized by peculiar poetics and melodics, and dramatic life experiences of their performers, attributing particular relevance to the keynote narrative of the misery. Rather than approaching ballads as a genre, the author treats them as a certain “register”, which also resonates in other folksongs and folk narratives, likewise being reflected by some circumstances in the life of their performers, such as widowhood, orphanage, singleness, grievance, and general misery. These are certain “ballad-like notes” in the performers’ lives. Therefore, the author views ballads and other folksongs from a special perspective, attempting to “insert” them into the everyday circumstances of the singers, weaving them together with the biographical facts of the performers or taking into consideration other relevant data. In other words, the authors attempts to broaden the scope of the ballad research by including the life stories of the performers, or at least fragments of these stories.However, although such terms as autobiographical narratives or life stories appear in the article, such personal experience narratives as those common in the modern folklore research that have become subject to analysis for several decades already, do not and even cannot emerge in this study. It is precisely because the legacy of all the performers introduced in this article comes from the second half of the 20th century (a little – also from the first half of it). At that time folklore collectors paid little attention to the life stories of the singers or storytellers, normally noting down only the most essential personal information. Only rarely more extensive autobiographical data supplied by the informants themselves are available. The main subject of the current study comprises mostly such fragmented and scarce material, or even separate facts, carefully picked out from the collectors’ remarks, memoires, and (auto) biographies.The folk singers mentioned in this article belong to the generation born approximately at the turn of the 19th and the 20th centuries, which grew up and learned the folksongs in the period of existence of the first independent Lithuanian Republic. Almost all of them lived in the so-called Vilnius Region, which at that time belonged to Poland. The majority of these performers are inhabitants of the southern part of the Vilnius Region, or Dzūkija.In terms of contextuality, all kinds of data regarding the “actual” context of the folklore pieces are important to their perception. By presenting biographical facts of the singers, the aim is not creating their exhaustive portraits, but rather viewing the folksongs in the light of the certain events from the lives of their performers. The author concludes that experience and memory of those events is able to alter the perception of the ballads. More broadly, this is the possible contemporary context of the ballads that has reached our times, enabling us to understand them better.
Keywords: -